Effect of sprinting velocity on anterior cruciate ligament and knee load during sidestep cutting - Moon, Jeheon; Koo, Dohoon; Kim, Sungmin; Panday, Siddhartha Bikram (Frontiers in Bioengineering and Biotechnology, 2023)
The purpose of the study was to investigate the effect of an increase in sprinting velocity on the anterior cruciate ligament (ACL) load, knee joint load, and activation of femoral muscles using the musculoskeletal modeling approach. Fourteen high school athletes were recruited (age: 17.4 ± 0.7 years, height: 1.75 ± 0.04 m, weight: 73.3 ± 8.94 kg), with the right foot dominant and physical activity level of about 3-4 hours per day. The kinematics, kinetics, and co-contraction index (CCI) of the extensors and flexors of the right leg's femoral muscles were calculated. The ACL load was estimated using the musculoskeletal modeling method. In the results, it was observed that the ACL load (p < 0.017) increased as sidestep cutting velocity increased, resulting in increased adduction (p < 0.017) and the internal rotation moment of the knee joint. This was significantly higher than when sprinting at a similar speed. The CCI result, which represents the balanced activation of the femoral extensor and flexor muscles, showed a tendency of decrement with increasing sprinting velocity during sidestep cutting (p 0.017), whereas no significant differences were observed when running at different sprinting conditions. Therefore, we postulate that factors such as knee joint shear force, extended landing posture with increasing sprinting velocity, internal rotation moment, and femoral muscle activity imbalance influence the increase of ACL load during a sidestep cutting maneuver.